The Effect of Tri Hita Karana Culture on The Organizational Commitment and Performance of The Company - Surya, Ida Bagus Ketut; Wijaya Kesuma, I Ketut; Kartika Dewi, AA. Sagung; Ayu Sriathi, AA. (Udayana Journal of Social Sciences and Humanities, 2017)
The purpose of this research is to explore the cultural influences of Tri Hita Karana to organizational commitment and the performance of the company. More specific aims are testing and analyzing the cultural influences of Tri Hita Karana on performance of company and organizational commitment role as mediation of the relationship between Tri Hita Karana to the performance of company. The data were collected by cross-section through questionnaires, the unit of analysis is the Regional Water Company of Tabanan Regency. Respondents are all leaders belonging to the management of as many as 42 people. The data analysis method used to test the hypothesis is Path Analysis. The results of this study indicate that a good implementation of Tri Hita Karana culture can improve the performance of the company. Good implementation of Tri Hita Karana culture can increase organizational commitment and at the same time improve the performance of the company Further organizational commitment proved to be mediating the cultural influence of Tri Hita Karana to company performance.It is recommended that the board of directors and management further promote the culture that is embraced to even be used as guidelines for PDAM of Tabanan regency.